Wãküsé: trajetórias da educação profissional e tecnológica em São Gabriel da Cachoeira-AM - Barreto, Roselinda Lima (Brasil, 2023)
The book Wãküsé: Trajectories of Professional and Technological Education (PTE) in São Gabriel da Cachoeira - AM is the result of an investigative process developed within the scope of the Professional and Technological Education Graduate Program - ProfEPT. Its materialization in E-book format constitutes a narrative and reflective synthesis that aims to embody the moments of construction and establishment of PTE in this region. Like a memorial, it indicates a path, not only with the intention of telling a story, but also of facilitating the understanding of the events that occurred based on its record. This condition also encourages those who were part of this process to express their experiences as a political element in this educational trajectory, which is so necessary for our regional singularity, spreading it to future generations and not allowing it to be consumed and forgotten by time. Its result expresses the perception of the subjects involved in the process, highlighting their moments of constitution. In this way, we dedicate this text to the entire educational community involved in PTE, such as teachers, researchers, and students, in order to problematize professional training and indicate other meanings to be used in the educational practices of our institutions.